Nostra Aetate: a personal reflection - Fisher, Eugene J. (Journal of ecumenical studies, 2015)
This essay weaves together the personal experiences of the author's life in Catholic-Jewish dialogue with a brief survey of relations on all levels between Jews and Christians. Acknowledging the efforts of Protestants as well as Catholics, it notes that the Jewish-Christian dialogue has been a major ecumenical effort in our time. Noting some of the problems and conflicts that have arisen in Catholic-Jewish relations, especially on the level of relations between the Holy See and the Jewish People, the author notes efforts made by both communities to resolve the difficulties and to establish teaching about each other that can be passed on to future generations, so that never again can the evil of Antisemitism hold sway among Christians.